Financial reckoning day : surviving the soft depression of the 21st century - Bonner, William; Wiggin, Addison (Hoboken, N.J. : John Wiley & Sons, 2003)
This pair of maverick investment writers shows that the key to surviving a soft depression is not collecting and analyzing current market data. Instead, if Americans want to plow through their financial woes and put some muscle back in their portfolios, they must look to the follies of the past.
Includes bibliographical references (p. 285-290) and index.
oif 21/08/15
Loan
Keywords: Financial crises; Stocks; Business cycles; United States